Respiratory diseases and associated factors: population-based study in São Paulo, 2008-2009 - Sousa, Clóvis Arlindo de; César, Chester Luiz Galvão; Barros, Marilisa Berti de Azevedo; Carandina, Luana; Goldbaum, Moisés; Pereira, Júlio Cesar Rodrigues (Revista de Saúde Pública, 2012)
OBJECTIVE: To assess the prevalence of acute bronchitis, rhinitis, and sinusitis among children and adolescents and identify associated factors. METHODS: This is a population-based, cross-sectional study. A household survey was conducted with 1,185 children and adolescents from the city of São Paulo (Southeastern Brazil), from 2008 to 2009. The participants were selected by means of probability sampling, stratified by sex and age, and by two-stage cluster sampling. For the adjusted analysis, multiple Poisson regression was used. RESULTS: Of the respondents, 7.3% reported acute bronchitis, 22.6% rhinitis and15.3% sinusitis. After the adjusted analysis, the following characteristics were associated with self;reported acute bronchitis: age 0 to 4 years (PR=17.86; 95%CI: 3.65;90.91), 5 to 9 years (PR=37.04; 95%CI: 8.13;166.67), 10 to 14 years (PR=20,83; 95%CI: 4.93;90.91), allergy (PR=3.12; 95%CI: 1.70;5.73), black and mixed-ethnicity (black and white) skin color (PR=2.29; 95%CI: 1.21;4.35), and living in a household with 1 to 3 rooms (PR=1.85; 95%CI: 1.17;2.94). As to self-reported rhinitis, the following characteristics were associated: age 10 to 14 years (PR=2.77; 95%CI: 1.60;4.78), 15 to 19 years (PR=2.58; 95%CI: 1.52;4.39), allergy (PR=4.32; 95%CI: 2.79;6.70), asthma (PR=2.30; 95%CI: 1.30;4.10) and living in flats (PR=1.70; 95%CI: 1.06;2.73). Concerning self-reported sinusitis, the following characteristics were associated: age 5 to 9 years (PR=2.44; 95%CI: 1.09;5.43), 10 to 14 years (PR=2.99; 95%CI: 1.36;6.58), 15 to 19 years (PR=3.62; 95%CI: 1.68;7.81), allergy (PR=2.23 (95%CI: 1.41;3.52) and obesity (PR=4.42; 95%CI: 1.56;12.50). CONCLUSIONS: Respiratory diseases were more prevalent in population groups with defined characteristics, such as age group, self-reported diseases, type of household and obesity.